The development, formulation and characterization of an optimized metronidazole loaded solid lipid nanoparticle formulation for ocular drug delivery - Sikhondze, Simise Siphelele (Rhodes University, Faculty of Pharmacy, Pharmacy)
Thesis embargoed. To be released early 2026.
Keywords: Uncatalogued